Response Solutions for a Singularly Perturbed System Involving Reflection of the Argument - Shanliang Zhu; Shufang Zhang; Xinli Zhang; Qingling Li (Advances in Mathematical Physics)
In this paper, the existence and uniqueness of response solutions, which has the same frequency ω with the nonlinear terms, are investigated for a quasiperiodic singularly perturbed system involving reflection of the argument. Firstly, we prove that all quasiperiodic functions with the frequency ω form a Banach space. Then, we obtain the existence and uniqueness of quasiperiodic solutions by means of the fixed-point methods and the B-property of quasiperiodic functions.